Mathematics in early years education - Montague-Smith, Ann; Price, Allison; Montague-Smith, Ann (London Routledge, 2012)
"This third edition of the best-selling Mathematics in Nursery Education provides an accessible introduction to the teaching of mathematics in the early years. Covering all areas of mathematics learning - number and counting, calculation, pattern, shape, measures and data handling - it summarises the research findings and underlying key concepts and explains how adults can help children to learn through practical experiences, discussion and more direct intervention. This new edition has been fully updated to incorporate the latest research and thinking in this area and covers: - why mathematics is important as a way of making sense of the world - how attitudes to mathematics can influence teaching and learning - how children learn mathematics - new material on sorting, matching and handling data - ideas for observation and questioning to assess children's understanding - examples of planned activities - suggestions for language development - assessment criteria. This textbook is ideal for those training to be teachers through an undergraduate or PGCE route, those training for Early Years Professional Status and those studying early childhood on foundation or honours degrees. This will be an essential text for any Early Years practitioner looking to make mathematics interesting, exciting and engaging in their classroom. "--Provided by publisher.
Revised edition of: Mathematics in nursery education, 1997.
Includes bibliographical references (pages 225-232) and index.
Keywords: Mathematics -- Study and teaching (Early childhood) -- Great Britain